Bibekacuṛāmaṇi : sarbaśāstra-siddhanta-sāmarasya - Caṭṭopādhyāẏa, Sudhīra Kumāra (Śaṅkara Hal eṇḍa Śaṅkara Insṭiṭiuṭ aph Philasaphi eṇḍa Kālcār, 1981)
Study of the basic tenets and universality of the Advaita philosophy as reflected in Śaṅkarācārya's Vivekacūḍāmaṇi.